Gold Nanorods: Evaporative Self‐Assembly of Gold Nanorods into Macroscopic 3D Plasmonic Superlattice Arrays (Adv. Mater. 13/2016). Issue 13 (1st April 2016) - Li, Penghui; Li, Yong; Zhou, Zhang‐Kai; Tang, Siying; Yu, Xue‐Feng; Xiao, Shu; Wu, Zhongzhen; Xiao, Quanlan; Zhao, Yuetao; Wang, Huaiyu; Chu, Paul K.
Abstract : On page 2511, X.‐F. Yu, P. K. Chu, and co‐workers demonstrate the successful fabrication of millimeter‐scale three‐dimensional superlattice arrays consisting of dense, regular, and vertically aligned gold nanorods by the evaporative self‐assembly method. The excellent performance in surface‐enhanced Raman scattering indicates applications in plasmonic substrates.